ASAS PROPORSIONALITAS DALAM PEMBAYARAN GANTI RUGI MELALUI ASURANSI DALAM KASUS MALPRAKTIK DOKTER - Ni Putu Ayu Myra Gerhana Putri (University of Udayana, 2013)
In a malpractice medical insurance context, indemnity obligations of malpractice,particularly for improper practice performed by medical team, currently only based onoverall team fault, means every physician in the team should bear the compensation evenly.This scheme is not fair because the physician who did lower degree of mistakes must bear thecompensation as great as the physician with higher degree of mistakes. That is whyproporsional concept, based on the degree of the mistakes, for indemnity obligations needs tobe considered. However, this scheme will need some instruments that can align theresponsibility among the physician in the team. This instrument then can be used as a basisfor determining the degree of mistakes and further the level of compensation the physicianneed to bear with. This research is a normative legal research and using a statue approach,means legislation as the primary legal materials. In addition, this research also uses books,articles, and materials from the Internet, as well as direct interview with the competentparties as a secunder data. The results showed that because there are no rules governing thelaw of proporsionality in the legislation make the degree of mistakes is not used as basis fordetermining the compensation’s level. In fact there are instruments that can be used as basisto determine the degree of mistakes such as Standard Operational Procedure (SOP) andMedical Professional Standard. It is clear that the healthcare legislation should includeprovisions that govern the determination of the compensation by using proportionalapproach, in order to align the responsibility among the parties